The Influence of Verbal-Linguistic Intelligence on Students Learning Outcomes in English at SMA Negeri 1 Sidrap - Handayani, Rini; Sakkir, Geminastiti; Kasman, Rosmini (EduLine: Journal of Education and Learning Innovation, 2021)
This study aims to determine verbal linguistic intelligence, to determine the results learning English especially on students' speaking, and to find out the influence of verbal linguistic intelligence on learning outcomes in English students of class X IPA 1 of SMAN 1 Sidrap. This research is quantitative research; this type of research is a pre-experimental design research. The population in this study was all students of class X SMAN 1 Sidrap, amounting to 182 people, while the study sample was the entire population, namely students of class X IPA 1 SMAN 1 Sidrap, amounting to 32 people. The instruments used in this study were interviews, questionnaires, treatment and recording tools. The data analysis technique used is descriptive statistical analysis and simple regression test through the application of SPSS. Based on the results of descriptive statistical analysis, verbal linguistic intelligence obtained an average value of 84.94, the lowest value obtained 0, and the highest value 107 and are at a percentage of 56.25% are in the average category. The results of learning English in this case speaking students obtained an average value of 96, the lowest value of 0, and the highest value of 96 and are in the good category with a percentage of 65.625%. The simple regression test results obtained sig <Î± (0,000 <0.05). This means that Ho is rejected and Ha is accepted, which means there is a positive influence between verbal linguistic intelligence on learning outcomes of students of class X Science 1 of SMAN 1 Sidrap.